Physician's Burnout and the COVID-19 Pandemic—A Nationwide Cross-Sectional Study in Austria - Kurzthaler, Ilsemarie; Kemmler, Georg; Holzner, Bernhard; Hofer, Alex (Frontiers in Psychiatry, 2021)
Objective: To assess the prevalence of burnout and psychological distress among general practitioners and private practice physicians of various specialities during the COVID-19 pandemic, and to identify contributing factors. Materials and Methods: Burnout and psychological distress were assessed with the Copenhagen Burnout Inventory (CBI) and the Brief Symptom Inventory (BSI-18). A newly developed self-reporting questionnaire was used to evaluate demographic data and pandemic-associated stress factors. Results: 252 general practitioners and 229 private practice physicians provided sufficient responses to the outcome variables for analysis. The prevalence of clinically relevant psychological distress was comparable between groups (12.4 vs. 9.2%). A larger proportion of general practitioners than specialists had intermediate or high burnout without reaching statistical significance for either category. When combining study participants with intermediate and high levels of burnout, the group difference attained significance (70.7 % vs. 61.9%). Being single, financial problems, and facing violence in patient care were identified as significant predictors of burnout and psychological distress. Furthermore, burnout was predicted by stigmatization because of treatment of SARS-CoV-2-positive patients and by longer working hours during the pandemic. Conclusion: Our findings provide evidence that practicing physicians are at high risk of burnout in the context of the pandemic. As physician burnout impairs performance and quality of professional services with consequences for physicians, healthcare organizations, and patient outcomes, health systems are prompted to prioritize physicians’ health and well-being directly.